[OP.LB03.05] REDUCING ARTERIAL STIFFNESS INDEPENDENTLY OF BLOOD PRESSURE: PROOF OF CONCEPT? THE RANDOMISED, FACTORIAL 'VASERA' TRIAL. (September 2016) - Mills, C.E.; Govoni, V.; Faconti, L.; Morant, S.; Casagrande, M.L.; Maskell, P.; Masani, A.; Crickmore, H.; Iqbal, F.; Webb, A.J.; Cruickshank, J.K.
Abstract : Objective: Arterial stiffness (AS) as pulse wave velocity (PWV) is a powerful index of prognosis, independent of blood pressure (BP) and could be an important treatment target; increased AS is a common finding in type-2 diabetes (T2D). Our hypothesis was that spironolactone and dietary nitrate in beetroot juice (via the nitrate-nitrite-nitric oxide pathway) would reduce AS independently of any BP change in patients with or at risk of T2D. Design and method: 126 patients were randomised double-blind to daily spironolactone (<50 mg) or doxazosin (control; < 16 mg), and 70 mL 'Beet-It' beetroot juice (<∼9 mmol nitrate) or nitrate-depleted beetroot juice (placebo; ∼0.3 mmol nitrate) over 6 months. Vascular measurements were performed at baseline, 3 and 6 months. Cardiac-Ankle Vascular Index (CAVI), a BP-independent measure of AS, by VaSera VS-1500N (Fukuda Denshi), was the primary outcome. Aortic (ao)PWV and BP were measured by Arteriograph as secondary outcomes. Intention-to-treat analysis was performed using SAS by mixed model 2-way ANOVA, adjusted as pre-specified for baseline outcome measure and difference in systolic (S), or mean, BP. Results: SBP reductions on spironolactone and doxazosin were similar (mean[95% CI]: −7.0 [−9.9, −4.2] vs. −6.3 [−9.1, −3.5] mmHg, p = 0.7). Spironolactone did not reduce AS, rather there was some evidence that doxazosin reduced CAVI (−0.11 [−0.30, 0.08] vs. 0.14 [−0.06, 0.34] units, p = 0.080), an effect statistically significant for aoPWV (−0.44 [−0.69, −0.20] vs. −0.07 [−0.32, 0.18] ms-2, p = 0.039). Dietary nitrate did not reduce CAVI, aoPWV or SBP, or increase circulating nitrite despite increasing plasma nitrate compared with placebo juice (165 [89.0, 240] vs. 3.21 [−4.64, 11.1] μM, p < 0.001). No interaction between treatments was detected. Conclusions: Contrary to our hypothesis and previous estimates, spironolactone did not reduce AS in this fully-controlled trial. Rather, aoPWV was reduced on doxazosin in these T2D and at-risk patients, after adjusting for, so independent of, BP difference between treatments over time. Conversion of nitrate to nitrite was hindered, blunting the beneficial effects of nitrate on BP and aoPWV previously seen in healthy volunteers and hypertensives. The VaSera trial was funded by Fukuda Denshi.